Comparative characteristic of the brain natriuretic peptide and angiotensin II expression index in the structure of locus coeruleus of brain stem in rats with arterial hypertension of various origins - M. V. Danukalo; O. V. Hancheva; Ye. V. Kadzharian (Patologìâ)
The aim of our study was to determine the characteristics of the BNP and AT II expression in the LC structure of rat brain stem with experimental (genetically determined essential and secondary endocrine-salt) arterial hypertension and to give a comparative description of the expression pattern of these peptides in etiologically different types of arterial hypertension.